WOOD CHARACTERIZATION OF Poincianella pyramidalis (TUL.) L.P. Queiroz - Paula, Yara Lemos de; Melo, Ronisson da Silva; Silva, Erick Daniel Gomes da; Alves, Allyson Rocha; Boschetti, Walter Torezani Neto; Holanda, Alan Cauê de; Alves, Rejane Costa (Science & Technology Journals, 2018)
The aim of this study was to determine the technological potential of catingueira, Poincianella pyramidalis (Tul.) L.P. Queiroz (Fabaceae) wood, a native plant of the Caatinga biome, in the Semiarid region, Brazil. For this purpose, the basic specific mass was determined, and the macroscopic and microscopic wood anatomical characterizations were performed. The methods used followed the NBR 11941, COPANT, IPT workbook, and IAWA recommendations. Catingueira wood shows density and anatomical characters that can serve for other applications than the use for energy generation only. Those information are also important to encourage new researches, to guide decision-making on the efficient use of this wood, and to strengthen the dialogue on the valuation and on the sustainable use of Caatinga species.
Keywords: catingueira; microscopy; multiple uses.